A Randomized, Controlled Trial of Early versus Late Initiation of Dialysis - Cooper, Bruce A; Branley, Pauline; Bulfone, Liliana; Collins, John F; Craig, Jonathan C; Fraenkel, Margaret B; Harris, David C; Harris, Anthony; Johnson, David W; Kesselhut, Joan; Li, Jing Jing; Luxton, Grant; et al. (The New England journal of medicine, 2010)
In this study, adults with progressive chronic kidney disease and an estimated glomerular filtration rate between 10 and 15 ml per minute per 1.73 m 2 (stage V chronic kidney disease) were randomly assigned to early or late initiation of dialysis. Early initiation of dialysis was not associated with an improvement in survival or clinical outcomes. The worldwide prevalence of long-term dialysis continues to rise, 1 , 2 driven in part by strong trends toward the initiation of dialysis earlier in the natural history of chronic kidney disease than was the practice previously. 3 – 5 Traditionally, the indicators for starting dialysis were the presence of signs and symptoms of uremia in combination with the results of biochemical measurements in serum and plasma. 6 However, a number of observational cohort and case–control studies have suggested that starting dialysis early may improve patients' survival, quality of life, and capacity for employment and decrease complications. 7 – 9 Although such studies were potentially limited by . . .